The rare case of a true rectovaginal fistula and its repair - Carly R. Richards; Nicole R. Lafferriere; Sidney M. Johnson (Elsevier, 2019)
Background: Within the spectrum of anorectal malformations, congenital rectovaginal fistulae are a rare but treatable entity. These less common variates can be treated much in the same fashion as other malformations such as imperforate anus or rectovestibular fistulae are repaired. Summary: In the case presented here, diagnosis of a rectovaginal fistula was delayed despite repeated examinations until the patient reached a size where the fistula was easily identifiable. The patient had no other anorectal malformation and was otherwise in good health. Her repair was done as a same day surgery and the patient recovered without complication. Conclusion: A rectovaginal fistula is a highly unusual clinical entity but one amenable to repair in the same fashion as other similar malformations. Keywords: Rectovaginal fistula, Anorectal malformation, Sagittal anorectoplasty